Records of Lonchaeidae (Diptera, Cyclorrhapha) from Togo and other African countries, with descriptions of new species - Macgowan, Iain; Tschirnhaus, Michael Von (Zootaxa, 2024)
Seventeen species of Lonchaeidae are recorded from the west African state of Togo amongst which are eight species new to science namely; Silba akloa sp. nov., Silba bambesa sp. nov., Silba kakamega sp. nov., Silba media sp. nov., Silba otandjobo sp. nov., Silba togoensis sp. nov., Silba tsifama sp. nov. and Silba zogbegani sp. nov. In addition, one new species, Fulgenta rwanda sp. nov., is added from material collected in Rwanda. Additional records are provided for the occurrence of the new species in Cameroon, Democratic Republic of Congo, Kenya and Uganda. The male terminalia of all species recorded are illustrated. An annotated checklist of the Lonchaeidae and a key to the Lonchaea and Silba species presently known from Togo are provided.